2023
DOI: 10.21638/spbu03.2023.206
|View full text |Cite
|
Sign up to set email alerts
|

Risk screening of non-native suckermouth armoured catfishes <em>Pterygoplichthys</em> spp. in the River Dinh (Vietnam) using two related decision-support tools

Abstract: The invasion risk of non-native suckermouth catfishes Pterygoplichthys spp. in the River Dinh (Vietnam) was evaluated using two related decision-support tools, namely the Fish Invasiveness Screening Kit (FISK) and the Aquatic Species Invasiveness Screening Kit (AS-ISK). The results of screenings obtained independently by three assessors using both toolkits were evaluated for consistency, and compared with a screening study previously obtained for Vietnam as a wide risk assessment area. Both FISK and AS-ISK bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…to new water bodies (Vander Zanden & Olden, 2008) and reducing further spread within invaded waterways, for example, the potential use of barriers as conservation tools (Rahel, 2013) and selectivity target Pterygoplichthys spp. during spawning migrations, in confined habitats, through continuous intensive fishing to reduce its population density (Chaichana & Jongphadungkiet, 2012); (4) studying the life history and behavioural traits and the physiological and hydraulic tolerances to identify potential control or eradication mechanisms (Zworykin & Đinh, 2023), for example, Australian researchers identified that invasive common carp Cyprinus carpio Linnaeus, 1758 jumped in constricted areas, while native fishes did not, and designed Williams' Cages to exploit this trait to reduce carp populations in Australia's waterways (Stuart et al, 2006);…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…to new water bodies (Vander Zanden & Olden, 2008) and reducing further spread within invaded waterways, for example, the potential use of barriers as conservation tools (Rahel, 2013) and selectivity target Pterygoplichthys spp. during spawning migrations, in confined habitats, through continuous intensive fishing to reduce its population density (Chaichana & Jongphadungkiet, 2012); (4) studying the life history and behavioural traits and the physiological and hydraulic tolerances to identify potential control or eradication mechanisms (Zworykin & Đinh, 2023), for example, Australian researchers identified that invasive common carp Cyprinus carpio Linnaeus, 1758 jumped in constricted areas, while native fishes did not, and designed Williams' Cages to exploit this trait to reduce carp populations in Australia's waterways (Stuart et al, 2006);…”
Section: Discussionmentioning
confidence: 99%
“…The taxonomic status for several Pterygoplichthys species is uncertain with P. ambrosettii (Holmberg, 1893), P. disjunctivus (Weber, 1991) and P. pardalis (Castelnau, 1855) currently considered part of the P. multiradiatus (Hancock, 1828) group (Zworykin & Đinh, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…From 13 to 15 March, captured fish from BW sampling location were transferred to the test chambers. Fourteen fish were used with a standard body length 16 ± 1.1 (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) cm and a body weight 100 ± 16.7 (20-202) g. In experiments, we used fish with a standard body length � 22 cm without catch damages. In total, 14 trials with 364 hours of video were assessed.…”
Section: Field Experimentsmentioning
confidence: 99%